Acchiappashpirt: xenoglossia concreta, performance sonora, poesia carnosa (ENTHYMEMA, 2020)
Acchiappashpirt is a poetronic duo crossing «contemporary music and avant-gard poetry» (as stated on their website). This article presents a viable path for identifying the extensions of contemporary Italian sound-poetry experimentalism through the emblematic experience offered by Acchiappashpirt. The collaboration between Jonida Prifti and Stefano Di Trapani started in 2008 and still progresses by continuously shifting the sensorial approach to the poetic code by rejecting fixi-ty as an instance, exalting the estrangement as a cognitive form of the self in relation to the world, and above all encouraging innovative critical approaches on relationships in order to create tension and desire towards the community.
Keywords: Acchiappashpirt; sound poetry; experimentalism; noise; contemporary Italianpoetry